DEVELOPMENT AND VALIDATION OF ATTENUATED TOTAL REFLECTANCE-FOURIER TRANSFORM INFRARED (ATR-FTIR) METHOD FOR DETERMINATION OF PEG 6000 CONTENT IN C-PHYCOCYANIN FRACTION - Rumondang Tamba, Silvia
C-phycocyanin (CPC) from Spirulina platensis is a blue protein-pigment that is widely used in various fields such as food, pharmaceuticals, cosmetics and others. One of the utilizations of CPC is developed as a substitute substrate in the determination of pancreatin protease (PP) activity. CPC isolated from purification using the ATPS method is still affected by PEG 6000. The presence of PEG 6000 causes the effect of enzyme activation. This study aims to develop an ATR-FTIR method for the determination of PEG 6000 levels in the CPC purification fraction. This research was conducted in several stages, namely CPC isolation, determination of measurement conditions with ATR-FTIR, validation, and method application. The isolation method was based on previous research and produced a CPC fraction with characteristics having a UV-Vis spectrum at a maximum wavelength of 620 nm, a content of 268.16 ?g/mL, and a purity value of 1.24. The sample was analyzed with ATR-FTIR at a spectral range of 4000 - 400 cm-¹, a resolution of 16 cm-¹, 16 scans, and a sample volume of 20 ?L. AUC was used for determination of levels and peaks were used in the range of 1180,22 – 983,518 cm-1. The validation results showed the method had good specificity; linearity with a correlation coefficient (r) value of 0.999 in the PEG 6000 concentration range of 10 - 45% (w/v); detection limit of 1,62% (w/v) and limit of quantitation of 5,41% (w/v). Accuracy results show the method has a percent recovery of 99,04 – 102,55%. Intraday and interday precision results resulted in a relative standard deviation of <2%. This validated method was used to determine the levels in four CPC fraction samples. The test results of PEG 6000 content in the samples ranged from 35,45 – 37,35% (b/v). The developed ATR-FTIR method can be used to determine the content of PEG 6000 in CPC fractions.